Effect of aging on the microstructure and toughness of the interface zone of a gas tungsten arc (GTA) synthesized Fe-Cr-Si-Mo-C coated low carbon steel - Korkut, MH; Yilmaz, O; Buytoz, S (Elsevier Science Sa, 2002)
Fe-Cr-Si-Mo-C alloy coatings have been developed by gas tungsten arc (GTA) processing on a low-carbon steel substrate. Depending on the processing parameters, either hypoeutectic or hypereutectic microstructures were formed, and at the interface martensitic, and martensite+pearlitic structures were obtained, In the interface between coated surface and alloy, the toughness was lower than coated surface and parent metal, To increase the toughness of the interface. aging processes were performed. The aging processing (480-550 degreesC) resulted in an increase in toughness of the interface between coated surface and the alloy. This behavior is related to a peak-hardening shift. M2C carbide coarsening. In addition the increased aging kinetics caused a faster dissolution of Fe3C and rapid changes in Cr partitioning in the (Mo.Cr)(2)C carbide resulting in a coherency loss. The kinetics of the secondary hardening reaction in the interface of the coating was determined by an electrical resistivity method for changes in aging parameters (time/temperature). (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: coating; GTA; low alloy steels; carbides; surfaces